2022
DOI: 10.1101/2022.02.21.481296
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Proteasomal downregulation of the pro-apoptotic MST2 pathway contributes to BRAF inhibitor resistance in melanoma

Abstract: The RAS-RAF-MEK-ERK pathway is hyperactivated in most malignant melanomas, and mutations in BRAF or NRAS account for most of these cases. BRAF inhibitors (BRAFi) are highly efficient for treating patients with BRAFV600E mutations, but tumours frequently acquire resistance within a few months. Multiple resistance mechanisms have been identified, due to mutations or network adaptations that revive ERK signalling. We have previously shown that RAF proteins inhibit the MST2 proapoptotic pathway in a kinase indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…The MST2 pathway role in melanoma is poorly understood and most studies have solely focussed on the role of YAP [38]. In a parallel study, we have seen that loss of expression of MST2 and LATS1 is common in melanoma cell lines that have acquired resistance to BRAF inhibitors [19]. We have demonstrated that oncogenic BRAF can inhibit MST1/2 in these cell lines and prevent the activation of its proapoptotic signal.…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…The MST2 pathway role in melanoma is poorly understood and most studies have solely focussed on the role of YAP [38]. In a parallel study, we have seen that loss of expression of MST2 and LATS1 is common in melanoma cell lines that have acquired resistance to BRAF inhibitors [19]. We have demonstrated that oncogenic BRAF can inhibit MST1/2 in these cell lines and prevent the activation of its proapoptotic signal.…”
Section: Discussionmentioning
confidence: 77%
“…2A). Since RASSF1A expression is lost in these cell lines [19,28,29], we postulated that the lack of expression of RASSF1A could impair LATS1 proapoptotic signalling in melanoma, explaining the resistance to LATS1 overexpression observed in these cell lines. Hence, we studied the effect that RASSF1A re-expression had in the regulation of MST2-LATS1 interaction in A375 cells.…”
Section: Expression Of Rassf1a Promotes Apoptosis and Lats1 Activatio...mentioning
confidence: 99%
See 3 more Smart Citations